1990
DOI: 10.1007/bf00017828
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical analysis of CaMV 35S promoter-?-glucuronidase gene expression in transgenic rice plants

Abstract: The cauliflower mosaic virus promoter is commonly used to drive transcription of chimeric genes in transgenic plants, including the cereals. To determine the tissue and cell types of cereal plants that the promoter functions in, transgenic rice plants containing a CaMV 35S promoter/GUS chimeric gene were analyzed for G U S activity. Insertion of a 35 S/GU S chimeric gene at low copy number into chromosomal DNA of plants regenerated from electroporated protoplasts was confirmed by gel blot hybridization analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(93 citation statements)
references
References 24 publications
5
85
0
1
Order By: Relevance
“…For this purpose, transient expression of the uidA reporter gene was evaluated under the control of a number of promoters. Although the CaMV 35S promoter has been shown to be active in most tissues of several plant species (26), in this research it was found to be the weakest of the promoters tested in sugarcane. While differences in transient gene expression level were observed among the monocot promoters, the highest activity was obtained with the Act1 promoter, which is in agreement with previous reports on the Act1-D promoter activity in other monocots such as date palm (16) and rice (27).…”
Section: Discussionmentioning
confidence: 52%
“…For this purpose, transient expression of the uidA reporter gene was evaluated under the control of a number of promoters. Although the CaMV 35S promoter has been shown to be active in most tissues of several plant species (26), in this research it was found to be the weakest of the promoters tested in sugarcane. While differences in transient gene expression level were observed among the monocot promoters, the highest activity was obtained with the Act1 promoter, which is in agreement with previous reports on the Act1-D promoter activity in other monocots such as date palm (16) and rice (27).…”
Section: Discussionmentioning
confidence: 52%
“…As the somatic embryos matured into plantlets, there was preferential expression of GUS in leaves over roots. Higher levels of GUS activity were found in leaves than in roots of rice (2) but not tobacco (3, 1 1) transformed with CaMV 35S-GUS constructions. The CaMV 35S promoter possesses domains that confer tissue-specific and developmentally regulated expression (3) that may be recognized differently in plants evolutionarily divergent from tobacco, such as rice and yellow-poplar, a member of the Magnoliaceae.…”
Section: Discussionmentioning
confidence: 88%
“…GUS histochemical staining was performed essentially as described previously (1,19). GUS activity was localized histochemically using a staining solution containing 1 mM X-Gluc (Sigma, Aldrich, MO), 50 mM sodium phosphate (pH 7.0), 10 mM sodium EDTA (pH 8.0), 0.5 mM potassium ferrocyanide, 0.5 mM potassium ferricyanide, 20% (vol/vol) methanol, and 0.05% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%